Degradation of antibiotic Cephalosporin C in different water matrices by ionizing radiation: Degradation kinetics, pathways, and toxicity - Chen, Xiaoying; Wang, Jianlong (The Science of the total environment, 2021)
Cephalosporin antibiotics are ubiquitous emerging pollutants in various aquatic environments due to their extensive production and application. Herein, the radiolytic degradation of antibiotic Cephalosporin C (CEP-C) in different water matrices was comprehensively investigated using gamma radiation at various experimental conditions. The results revealed that CEP-C oxidation obeyed pseudo first-order kinetics, and 100%, 94.9%, 67.0%, 44.6% and 34.5% removal of CEP-C with 10–200 mg/L was achieved at 0.4 kGy, respectively. The degradation was faster at higher absorbed dose and acidic conditions (pH = 3.5). The inorganic anions, including SO42−, NO3−, and HCO3−, had negative influence on the degradation of CEP-C, the corresponding rate constant decreased from 4.603 to 3.667, 1.677 and 2.509 kGy−1 respectively in the presence of SO42−, NO3−, and HCO3−. The analysis of intermediate products indicated that CEP-C was oxidized to generate about 10 intermediate products. Besides, it was inferred that the thioether sulfur oxidation, β-lactam ring opening, acetyl dissociation from dihydrothiazine ring and D-α-aminohexylamide group abscission were the major reaction mechanisms of CEP-C degradation by gamma radiation. Importantly, the antibacterial activity of CEP-C could be completely vanished by gamma radiation alone, while more toxic intermediate products might be formed. Addition of hydrogen peroxide and peroxymonosulfate could significantly improve the CEP-C degradation, and reduce the toxicity of intermediates of CEP-C degradation. Similar degradation behavior was observed in the groundwater and wastewater, implying that ionizing radiation can be used for degradation of Cephalosporin in water and wastewater. [Display omitted] •Radiolytic degradation of Cephalosporin C in different water matrices was studied.•CEP-C degradation obeyed pseudo first-order reaction kinetics.•Inorganic anions had negative effect on the degradation of Cephalosporin C.•The major mechanisms of CEP-C degradation by gamma radiation was proposed.•Ionizing radiation is effective for Cephalosporin degradation in water and wastewater.